Coastline Accuracy Assessment Developed By Using Multi Data Source - Nadya Oktaviani; Prayudha Hartanto; Ratna Sari Dewi; Danang Budi Susetyo; Sandi Aditya; Irmadi Nahib; Hollanda Arief Kusuma (Politeknik Negeri Batam, 2023)
Coastline Modeling Accuracy Assessment Developed By Using from Multi-Source Data. The coastal regions need to be developed because many big cities in Indonesia are located in these areas. However, it is crucial to determine the distance from the beach that is safe as the requirement for development along the coastal zone. The term of the beach is very closely affiliated with the coastline. The method of determining the coastline continues to be developed to fulfill the many needs related to the coastline. The coastline has a dynamic position. The land contour along the coast and the tide's state become several things that affect the coastline. Therefore, a dynamic model is required to define coastline positioning because both conditions are easy to change. The coastline determination from multi-source data modeling using DEM results is rarely done. In this study, coastline determination uses land height contours combined with sea depth contours and uses Mean Sea Level (MSL) value for vertical reference using the DEM model. The model's accuracy is tested by comparing the coastline delineation model and the Geospatial Information Agency coastline to test the DEM model generated before determining the coastline using this model as the reference. Based on this study, the compared shoreline models and delineation have gaps. This gap might be influenced by the data source, the model's resolution, and the data collection method.